THE FINTECH ECOSYSTEM AS AN INSTRUMENT FOR TRANSFORMING THE TRADITIONAL BANKING SYSTEM - Shirinova Shokhsanam; Otabek Muhammedov (Scholar Express Journals, 2024)
Over the past decades, banking has been advancing customer service by facilitating straightforward, secure, and short-term transactions. However, the COVID-19 pandemic has pushed the sector to adapt further and streamline access to its services. Digitalization, defined as the process of digitally transforming a business or company (Gartner, 2020), has gained popularity both as a business strategy and as a means to envision and drive future company transformations. Thanks to new developments, consumers have started to demand better customer service, more speed, transparency and a long list of new features. The study aims to pinpoint the key innovative areas where banking digitalization is expected to occur in the near future. Technological advancements are driving structural changes across all sectors of the global economy. For banks, digital transformation has become essential, not merely an option, to stay competitive and address the increasing demands of customers. This underscores the importance of comprehending the trends that will shape the future development of the banking system.
Keywords: Digital transformationcustomer service advancements; COVID-19 impact; service simplification